Removal of Organic Pollutants from San Pablo Farm Wastewater Using a Pilot-Scale Biological Treatment (2017)
Biological treatment is the most common process used to treat organics-containing wastewaters from industrial, domestic and agricultural activities. This work aims to remove organic pollutants using pilot-scale biological treatment system based on activated sludge. In addition, physical, chemical and microbiological characteristics of San Pablo Farm wastewaters were determined through analyses such as COD, DO, VSS, TSS and BOD and kinetic parameters were calculated by monod model. It was observed a significant decrease of this contaminant load in wastewater, achieving removal yields of 98% of BOD, 93% of COD and 99% of total coliforms. Kinetic coefficients obtained at pilot-scale registered similar values to those described by other researches and reveal a good performance of activated sludge in wastewater treatment.